1982
DOI: 10.1038/bjc.1982.250
|View full text |Cite
|
Sign up to set email alerts
|

The induction of rat bladder cancer by 2-naphthylamine

Abstract: Summary.-The widely held belief that 2 -naphthylamine is not carcinogenic for the rat has been re-examined. Twenty female Wistar rats were dosed by gastric intubation weekly for 57 weeks with 2 -naphthylamine, 300 mg/kg body wt, in arachis oil and 20 controls were given arachis oil alone. Animals which became moribund were killed during the course of the experiment and the remainder after 100 weeks. A 2-naphthylamine -treated animal died at 21 weeks; all others survived 57 weeks or longer. The urinary tracts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Similarly, the rat has for many years been considered resistant to the bladder carcinogen 2-naphthylamine (6). But Hicks and her colleagues (7) showed that using test conditions that favored the production of the active metabolite (i.e., high doses given at less frequent intervals rather than low doses given continuously), 2-naphthylamine is an effective rat bladder carcinogen. Overall, metabolism per se has not been shown to be a key factor in identifying agents active in animals but inactive in humans.…”
Section: Nonrelevant Animal Carcinogensmentioning
confidence: 99%
“…Similarly, the rat has for many years been considered resistant to the bladder carcinogen 2-naphthylamine (6). But Hicks and her colleagues (7) showed that using test conditions that favored the production of the active metabolite (i.e., high doses given at less frequent intervals rather than low doses given continuously), 2-naphthylamine is an effective rat bladder carcinogen. Overall, metabolism per se has not been shown to be a key factor in identifying agents active in animals but inactive in humans.…”
Section: Nonrelevant Animal Carcinogensmentioning
confidence: 99%
“…Some of these compounds are able to induce tumours, particularly in the urinary bladder of humans and animals 1,2) . Among them, benzidine, 2-naphthylamine, and 4-amino-biphenyl, are the most important carcinogenic substances which are also present in tobacco smoke.…”
mentioning
confidence: 99%
“…Wistar rats (20 females) were exposed to 2-NA at a dose of 300 mg/kg b.w. once a week for 57 weeks via gavage (in arachis oil) [101], with 20 rats serving as the control group. One moribund animal was killed.…”
Section: Oral Administrationmentioning
confidence: 99%